ANALISIS PERUBAHAN PSAK 24 KE PSAK 219 IMBALAN KERJA DAN DAMPAK YANG TIMBUL TERHADAP TRANSPARANSI LAPORAN KEUANGAN DI INDONESIA - Novi Rahmadani; Kensani Laras Sekar; Kaela Atifa Armanny; Riska Amelia Arief; Rinny Meidiyustiani (CV. Denasya Smart Publisher, 2026)
The revision of financial accounting standards in Indonesia demonstrates an effort to maintain transparency and conformity with global practices. This study aims to analyze the evolution and implementation of Statements of Financial Accounting Standards, relating to employee compensation, particularly the transition from Statements of Financial Accounting Standards 18 to 226 and from Statements of Financial Accounting Standards 24 to 219. The method applied is desk research of literature, regulations, and updates released by the Indonesian Financial Accounting Standards Board (FASB IAI). The research findings indicate that these Statements of Financial Accounting Standards revisions aim to improve the relevance, accuracy, and comparability of financial statements, particularly regarding the disclosure of pension obligations and benefits. Statements of Financial Accounting Standards 226 offers more comprehensive guidance on reporting pension benefit plans, while Statements of Financial Accounting Standards 219 highlights the importance of transparency in the recognition and valuation of employee benefits. These updates lead to improvements in the quality of financial reporting, but also require companies to adjust their accounting systems, strengthen collaboration with actuaries, and enhance human resource capacity in the accounting sector. Overall, the revision of Statements of Financial Accounting Standards on employee benefits is a crucial step towards improving the accountability and reliability of financial statements in Indonesia.